(Inter) relations between literacy practices in the writing of narratives in German and Portuguese by children living in the context of German as a heritage language - Rosenbrock, Emilia; Fritzen, Maristela Pereira; Heinig, Otília Lizete de Oliveira Martins (Pandaemonium Germanicum, 2017)
This article discusses some of the results of a broader research which aimed at understanding (inter) relationships established between reading and writing practices in German and Portuguese languages of primary school children and the context of inheritance language where they are inserted. For the theoretical dimension, the study follows the perspectives of Applied Linguistics and Education, focusing intercultural contexts. This qualitative-interpretative research had as setting a municipal school located in a rural area of the city of Blumenau, Santa Catarina. Regarding the methodological procedures, two proposals were used to produce written narratives, one in Portuguese and the other in German language. The results suggest that (i) children have limited dominance of the narrative structure, applying it partially in productions in both languages; (ii) vocabulary and grammatical structures are characteristics of everyday ordinary language practices; (iii) students are not aware of or they have not internalized spelling rules especially in German. The results of the research affirm the importance of guaranteeing the learning of the inheritance language in formal education, alongside Portuguese, in similar bi/multilingual contexts.